Overexpression of the long non-coding RNA Oprm1 alleviates apoptosis from cerebral ischemia-reperfusion injury through the Oprm1/miR-155/GATA3 axis. Issue 1 (4th December 2019) - Jing, Hongyu; Liu, Lingyun; Jia, Ye; Yao, Hanxin; Ma, Fuzhe
Abstract: Numerous differentially expressed long non-coding RNAs (lncRNAs) have been identified in cerebral ischemia-reperfusion (I/R) injury using RNA-Seq analysis. However, little is known about whether and how lncRNAs are involved in cerebral I/R injury. In this study, we investigated the function of the lncRNA Oprm1 in cerebral I/R injury and explored the underlying mechanism. An oxygen-glucose deprivation model in N2a cells was utilized to mimic cerebral I/R injury in vitro . Trypan blue staining, terminal deoxytransferase-mediated dUTP-biotin nick end labelling and caspase-3 were measured to evaluate apoptosis. Middle cerebral artery occlusion was performed in mice to evaluate the function of lncRNA Oprm1 in vivo . Real-time PCR and western blotting were used to measure the expression levels of lncRNA Opmr1, caspase-3, miR-155, GATA binding protein 3 (GATA3) and nuclear factor (NF)-κB. lncRNA Oprm1 was mainly located in the cytoplasm. Overexpression of lncRNA Oprm1 alleviated the apoptosis induced by oxygen-glucose deprivation and significantly reduced cleaved caspase-3 levels. Infarct size was distinctly decreased in the lncRNA Oprm1-overexpression group. The neurological score was also improved. Our findings showed that the lncRNA Oprm1/miR-155/GATA3 axis plays an important role in cerebral I/R injury. lncRNA Oprm1 may attenuate cerebral injury through the NF-κB pathway. lncRNA Oprm1 may serve as a potential target for new therapeutic interventions in patients with ischemic stroke.